2022
DOI: 10.1038/s41598-022-13080-w
|View full text |Cite
|
Sign up to set email alerts
|

Simple and practical methods for utilizing parylene C film based on vertical deposition and laser patterning

Abstract: We propose two novel methods to effectively utilize parylene C films. First, we demonstrate a vertical deposition method capable of depositing a parylene C film of the same thickness on both sides of a sample. Through this method, we have formed parylene C films with a thickness of 4 μm on both sides of the sample with a thickness deviation of less than 2.5%. Further optical verification indicates that parylene C films formed by this method have a very uniform thickness distribution on each side of the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Coclite et al used initiated plasma enhanced chemical vapor deposition(iPECVD) of an organosilicon polymer (1,3,5-trivinyl-1,1,3,5,5-pentamethyltrisiloxane (TVTSO) monomer) to planarize silicon substrates and demonstrated that when the organic thin film is 1.8 nm thick, a 99% degree of global planarization could be achieved. 108 For graphene film growth by atmospheric pressure CVD on copper foil, the final graphene film's homogeneity and electronic transport properties were found to be strongly influenced by the surface morphology of the Cu substrate and the concentration of carbon feedstock gas, as reported by Luo et al 110 Template for Organic Materials Thieme 107 (Reproduced from Ref. [107] with permission.…”
Section: Processing Technologiesmentioning
confidence: 84%
See 4 more Smart Citations
“…Coclite et al used initiated plasma enhanced chemical vapor deposition(iPECVD) of an organosilicon polymer (1,3,5-trivinyl-1,1,3,5,5-pentamethyltrisiloxane (TVTSO) monomer) to planarize silicon substrates and demonstrated that when the organic thin film is 1.8 nm thick, a 99% degree of global planarization could be achieved. 108 For graphene film growth by atmospheric pressure CVD on copper foil, the final graphene film's homogeneity and electronic transport properties were found to be strongly influenced by the surface morphology of the Cu substrate and the concentration of carbon feedstock gas, as reported by Luo et al 110 Template for Organic Materials Thieme 107 (Reproduced from Ref. [107] with permission.…”
Section: Processing Technologiesmentioning
confidence: 84%
“…108 For graphene film growth by atmospheric pressure CVD on copper foil, the final graphene film's homogeneity and electronic transport properties were found to be strongly influenced by the surface morphology of the Cu substrate and the concentration of carbon feedstock gas, as reported by Luo et al 110 Template for Organic Materials Thieme 107 (Reproduced from Ref. [107] with permission. Copyright 2022 Springer Nature.)…”
Section: Processing Technologiesmentioning
confidence: 84%
See 3 more Smart Citations